New integrative tool for assessing vulnerable urban areas. Refurbishment model for energy self-sufficient and bio-healthy neighbourhoods. Madrid, Spain. HABITA-RES - Alonso, Carmen; Martín-Consuegra, Fernando; Oteiza, Ignacio; De Frutos, Fernando; González-Cruz, Eduardo; Cuerdo-Vilches, Teresa; Frutos, Borja; Pérez, Gloria; Fernández-Agüera, Jessica; Dominguez-Amarillo, Samuel (Frontiers in Built Environment, 2023)
The research conducted under HABITA-RES explored the advisability of the integrative refurbishment of urban neighbourhoods on the outskirts of Madrid built between the end of the Civil War in 1939 and the enactment of the country’s first building code on the indoor environment in 1979. Characterised by highly inefficient buildings, many such neighbourhoods are listed as vulnerable urban areas. The study described hereunder analysed the feasibility of their conversion to energy self-sufficiency to improve residents’ environment, social circumstances and health. European directives and domestic legislation on energy production are introducing increasingly demanding requirements geared to achieving nearly zero energy buildings in 2020 and cities’ carbon neutrality by target year 2050. Possible approaches to achieve those ends were assessed under this study. The theoretical model used was validated with detailed information collected in situ on both social circumstances and energy efficiency. Designed to study improvement strategies for both individual and groups of buildings, the model prioritises passive improvements to lower demand. The findings will enable residents in such neighbourhoods to participate actively in improvement measures and access information on their costs and benefits.